Shifting Towards Trauma- and Violence-informed Care in the Early Learning and Childcare Sector: An Exploratory Study in Western Canada - Gerlach, Alison J.; Moosa-Mitha, Mehmoona; Macasaquit, Mariel; Slemon, Allie (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2026)
Early learning and childcare (ELCC) programs provide a critical context for responding to young children experiencing trauma. In shifting beyond an individualistic framing of trauma, this study explored how the emerging concept of trauma-and violence-informed care (TVIC) can be implemented in ELCC programs. Methods included interviews with early childhood educators, a parent focus group and walk-through of an ELCC centre, and participant observation. Analysis identified “a shared understanding of trauma” as foundational to implementing TVIC. Other themes included “changing the way we work with families,” “(re)designing spaces,” and “taking care of the carers.” Program- and practice-level implications are discussed.